Pengelolaan Cagar Budaya untuk Kepentingan Publik di Kabupaten Gianyar, Bali - ., Zuraidah (Pustaka : Jurnal Ilmu-Ilmu Budaya, 2018)
This study aims at finding the management of cultural heritages which are publically utilized. The locations of the study are Pegulingan temple, TirtaEmpul temple, Mengening temple, GunungKawi temple, and Goa Gajah. There are two stages of method applied in the study. The first, method and technic of collecting data (observation, interview and library study); the second isthe method ofqualitative data analysis. The results of the study show that the management applied to the five cultural heritages is the combination of management between the government (the District of Gianyar and BPCB Bali) and the local people. The involvement of the local people shows the application of the concept of CRM in which the people are benefited by the existence the archeological sites around their residences.